2017
DOI: 10.1111/pce.13104
|View full text |Cite
|
Sign up to set email alerts
|

SolarUV‐Bradiation and ethylene play a key role in modulating effective defenses againstAnticarsia gemmatalislarvae in field‐grown soybean

Abstract: Solar UV-B radiation has been reported to enhance plant defenses against herbivore insects in many species. However, the mechanism and traits involved in the UV-B mediated increment of plant resistance are unknown in crops species, such as soybean. Here, we studied defense-related responses in undamaged and Anticarsia gemmatalis larvae-damaged leaves of two soybean cultivars grown under attenuated or full solar UV-B radiation. We determined changes in jasmonates, ethylene (ET), salicylic acid, trypsin protease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 64 publications
(85 reference statements)
1
17
0
Order By: Relevance
“…post-herbivory) jasmonate levels, resulting in reinforced chemical defenses (Đinh et al ., 2013; Qi et al , 2018). Recently, Dillon et al (2018) reported enhanced induction of ET by combined solar UV-B and herbivory, and highlighted its possible role in soybean defenses. Less is known about the roles of SA, auxin, and ABA in UV-mediated induction of plant defenses.…”
Section: Introductionmentioning
confidence: 99%
“…post-herbivory) jasmonate levels, resulting in reinforced chemical defenses (Đinh et al ., 2013; Qi et al , 2018). Recently, Dillon et al (2018) reported enhanced induction of ET by combined solar UV-B and herbivory, and highlighted its possible role in soybean defenses. Less is known about the roles of SA, auxin, and ABA in UV-mediated induction of plant defenses.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, increases in the JA and ethylene burst has been described after combined UV-B exposure and aboveground herbivory, resulting in enhanced plant resistance. [9][10][11][12][13][14] Recently, we have demonstrated that supplemental UV (A + B) (λ 280-400 nm) can enhance tomato (Solanum lycopersicum) resistance to thrips (Frankliniella occidentalis),…”
mentioning
confidence: 99%
“…N. viridula herbivory phosphorylated and activated the mitogen-activated protein kinase (MAPK) pathway and induced an early peak of jasmonic and salicylic acid accumulation and ethylene emission in developing seeds of field-grown soybean; this up-regulated plant defenses and reduced stink bug preference 21 . Ethylene emission in soybean pods induced isoflavonoids, which are an effective defense against stink bugs 32 , 37 . Moreover, N. viridula feeding led to seed cell wall thickening as well as to increased expression of genes coding for expansine, xyloglucan endo-transferase, pectate lyase and polygalacturonase, all involved in the relaxation and restructuration of the cell wall 24 .…”
Section: Discussionmentioning
confidence: 99%